Who Are the Turkers? A Characterization of MTurk Workers Using the Personality Assessment Inventory. (July 2019) - McCredie, Morgan N.; Morey, Leslie C.
As online data collection services such as Amazon's Mechanical Turk (MTurk) gain popularity, the quality and representativeness of such data sources have gained research attention. To date, the majority of existing studies have compared MTurk workers with undergraduate samples, localized community samples, or other Internet-based samples, and thus, there remains little known about the personality and mental health constructs of MTurk workers relative to a national representative sample. The present study addresses these limitations and broadens the scope of existing research through the use of the Personality Assessment Inventory, a multiscale, self-report questionnaire which provides information regarding data validity and personality and psychopathology features standardized against a national U.S. census–matched normative sample. Results indicate that MTurk workers generally provide high-quality data and are reasonably representative of the general population across most psychological dimensions assessed. However, several distinguishing features of MTurk workers emerged that were consistent with prior findings of such individuals, primarily involving somewhat higher negative affect and lower social engagement.